RISK ASSESSMENT OF DAM MANAGEMENT: A CASE STUDY ON THE SEMANTOK DAM MANAGEMENT UNIT - Apriana, Yossi; Nurkholis , Nurkholis; Prihatiningtyas , Yeney Widya (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study aims to assess the risks associated with the operation and maintenance activities of the Semantok Dam Management Unit (Unit Pengelola Bendungan, UPB) to support sustainable management. The method employed is a qualitative case study approach using Risk Failure Mode and Effects Analysis (RFMEA), which prioritizes risks based on Risk Score and Risk Priority Number (RPN). The results identified five main risks: (1) suboptimal irrigation services due to limitations in the water distribution network; (2) a mismatch between AKNOP values and actual needs and budget; (3) illegal structures along the dam embankment that interfere with monitoring functions; (4) inaccuracies in monitoring analysis due to insufficient human resource competence; and (5) the presence of wild plants that can interfere with visual inspections and potentially damage the dam structure, exacerbated by insufficient maintenance personnel. This study addresses a gap in the literature, which has primarily focused on technical risks or risks during the construction phase. The application of RFMEA in the context of dam management expands the scope of this method, which has been widely used in the industrial sector and project management. The findings provide important considerations for risk-informed budget planning, particularly in the formulation of the Operational and Maintenance Actual Need Value (AKNOP), ensuring that allocations reflect real-world, on-site requirements. Furthermore, policies are needed to strengthen the capacity of dam management units through targeted training, certification, increased personnel, and improved analysis of monitoring data. Lastly, policies to protect reservoir buffer zones should be reinforced, both through enhanced physical surveillance and legal approaches, to prevent illegal occupation and associated risks.